Raye's group on mountains [camera roll 76 and sound roll 57 synchronized] (1978)
[00:04:20] Footage begins, shows the A/V operators [00:04:52] Brief explanation of the groups plan for the hike [00:05:49] Shot of Avila Beach [00:06:12] Footage stops, but audio remains [00:07:52] Footage returns with a shot of Avila Beach [00:08:34] Footage stops, but audio remains [00:10:50] Footage returns with a shot of the hillside; they are trying to plan out their path [00:11:23] Footage stops, but audio remains [00:12:09] Footage returns, and they are still planning their route [00:12:21] Conversation about the police [00:13:45] Footage stops, but audio remains [00:14:09] The group stop to rest [00:18:36] Footage returns, the group begins to hike again [00:20:54] Footage stops, but audio remains [00:20:20] Footage returns, there are various shots of the area, and they are planning their route [00:23:35] Helicopter hoovers overhead while the group gathers [00:25:35] Group holds hands in a circle, they have a meeting about where to go [00:27:13] Conversation about the potential of deer poachers nearby with rifles [00:27:51] Footage stops, but audio remains [00:32:07] Footage returns with the group at the top of the hill [00:33:21] Footage ends